Art Music by Caribbean Composers: Aruba - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Most Aruban cultural traditions are the result of the intermingling of the diverse heritages of its inhabitants (Razak, 2005).Musical influences in Aruba are likewise varied, though the most major influences are “African rhythms and European melodies” (Razak, 2005, para. 3). European-influenced dance music exists in the forms of the “Aruban waltz, the danza, the mazurka and the tumba” (Razak, 2005, para. 4). One uniquely Aruban musical tradition is the dande. Dande is a part of Aruban New Year's celebrations, during which groups of musicians visit the homes of friends, family and other members of their community to present holiday greetings in song and music (Razak, 2005).